Soluble interleukin 6 receptor levels are associated with reduced myocardial reperfusion after percutaneous coronary intervention for acute myocardial infarction. Issue 2 (June 2015) - Groot, Hilde E.; Hartman, Minke H.T.; Gu, Youlan L.; de Smet, Bart J.G.L.; van den Heuvel, Ad F.M.; Lipsic, Erik; van der Harst, Pim
Highlights: IL-6R signalling might play a causal role in the development of cardiac dysfunction. We studied the association of sIL-6R receptor levels with myocardial reperfusion. sIL-6R levels fluctuated biphasic during the two weeks after STEMI. Fluctuation was more pronounced in patients with reduced myocardial reperfusion. Larger change in sIL-6R levels was associated with reduced myocardial reperfusion. Abstract: Aims: Interleukin-6 receptor (IL-6R) signalling has been suggested to play a causal role in the development and outcome of coronary heart disease (CHD). The aim of this study was to investigate the association of sIL-6R levels with myocardial reperfusion after percutaneous coronary intervention (PCI) for acute ST-elevated myocardial infarction (STEMI). Methods: Blood was sampled from 70 patients presenting with STEMI at 6 different time-points (baseline, post-PCI, t = 1 h, t = 6 h, t = 24 h, t = 2w). Coronary angiograms post-PCI were analysed for myocardial blush grade (MBG) as indicator of myocardial reperfusion. Serum IL-6 and sIL-6R were measured using IL-6 and sIL-6R enzyme-linked immunosorbent assays (ELISA). Results: sIL-6R levels fluctuated biphasic during the two weeks after STEMI. Reduced MBG was associated with a larger change in sIL-6R levels between baseline and post-PCI compared to optimal MBG (−13.40; SEM 2.78 ng/ml vs −1.99; SEM 2.35 ng/ml, respectively; p < 0.001). Patients with reduced MBG also showed a larger increase in sIL-6R levels after PCI and 1 h after myocardial infarction (MI) compared to optimal MBG (respectively 11.56; SEM 2.68 ng/ml vs 3.02; SEM 2.39 ng/ml; p = 0.018). IL-6/sIL-6R ratio was also more increased in patients with reduced MBG at 24 h after myocardial infarction (0.23; SEM 0.08–0.51 vs 0.10; SEM 0.05–0.21; p = 0.024). An optimal MBG was associated with a 10 ng increase in sIL-6R level between baseline and post-PCI (OR 1.687, CI 1.095–2.598; p = 0.018). Conclusions: sIL-6R levels fluctuate biphasic during the two weeks after MI with larger changes and increased IL-6/sIL-6R ratio in patients with reduced MBG. Further research is needed to increase our understanding of the possible causality of these associations.